2016
DOI: 10.1097/md.0000000000005639
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein E concentration and polymorphism influence serum lipid levels in Chinese Shandong Han population

Abstract: Apolipoprotein E (ApoE), which has been shown to influence serum lipid parameters, can bind to multiple types of lipids and plays an important role in the metabolism and homeostasis of lipids and lipoproteins. A previous study showed that ApoE concentration significantly affects serum lipid levels independently of ApoE polymorphism. The serum lipid levels were also closely correlated with dietary habits, and Shandong cuisine is famous for its high salt and oil contents, which widely differ among the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
(22 reference statements)
4
21
2
1
Order By: Relevance
“…The allele frequencies of the APOE polymorphisms (E2 7.11%, E3 79.56%, E4 13.33%) in this study were similar to previous reports among the Thai population (E2 7.18%‐10.42%, E3 77.04%‐77.51%, E4 12.54%‐15.43%) . APOE4 allele in our study was higher than Japanese (10.5%), Han Chinese (7.5%), Taiwanese (7.5%), and Korean (9%) populations but lower than the Malaysian population (20.20%) . These inconsistent results may be due to the specific populations.…”
Section: Discussioncontrasting
confidence: 81%
“…The allele frequencies of the APOE polymorphisms (E2 7.11%, E3 79.56%, E4 13.33%) in this study were similar to previous reports among the Thai population (E2 7.18%‐10.42%, E3 77.04%‐77.51%, E4 12.54%‐15.43%) . APOE4 allele in our study was higher than Japanese (10.5%), Han Chinese (7.5%), Taiwanese (7.5%), and Korean (9%) populations but lower than the Malaysian population (20.20%) . These inconsistent results may be due to the specific populations.…”
Section: Discussioncontrasting
confidence: 81%
“…In the Chinese population, the predominant genotype is E3/ E3 in the Chinese population, whereas the most common allele is E3, followed by E2/E3, E3/E4, E2/E4, E4/E4, and E2/E2. [23][24][25] Our research also confirmed that E3/E3 and E3 were dominant. However, in this research, the E3/E4 genotype follows the E3/E3 genotype in WML group and brain atrophy group, respectively, but the E2/E2 genotype follows the E2/E3 genotype in the co-occurrence of WML and brain atrophy disease group.…”
Section: Discussionsupporting
confidence: 80%
“…For example, the ApoE gene, APOE, is located on chromosome 19, and has three common alleles that encode three isoforms: ApoE2, ApoE3, and ApoE4. The ApoE2 and ApoE4 isoforms have been reliably associated with high triglyceride and VLDL levels [27,36]. Therefore, it has been postulated that APOE gene polymorphisms are associated with an increased risk of both cardiovascular disease and pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%